2020
DOI: 10.2139/ssrn.3708098
|View full text |Cite
|
Sign up to set email alerts
|

Economic Uncertainty and Bank Stability: Conventional vs. Islamic Banking

Abstract: In this paper, we explore whether economic uncertainty differently affects the default risk of Islamic and conventional banks. Using a sample of 568 banks from 20 countries between 2009 and 2018, we take advantage of the World Uncertainty Index (WUI) proposed by Ahir et al. (2018) to conduct a study based on a comparable measure across countries. Our findings indicate that, while economic uncertainty increases the default risk of conventional banks, Islamic banks' default risk is not affected. To shed light on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the sectors financed by Islamic banks may have been disproportionately affected by the pandemic, exacerbating the impact on non-performing financing \ (Khoirotunnisa & Zulfikar, 2022). Islamic banks' operational risk, including legal and Sharia compliance risks, may pose additional challenges compared to conventional banks, impacting their ability to navigate economic shocks effectively (Bilgin et al, 2020). The study by (Rashid et al, 2017) suggests that Islamic banks have performed better than conventional banks in contributing to financial stability, indicating a potential resilience in the face of crises (Rashid et al, 2017).…”
Section: Greater Negative Impact On Islamic Banks Compared To Convent...mentioning
confidence: 99%
“…Additionally, the sectors financed by Islamic banks may have been disproportionately affected by the pandemic, exacerbating the impact on non-performing financing \ (Khoirotunnisa & Zulfikar, 2022). Islamic banks' operational risk, including legal and Sharia compliance risks, may pose additional challenges compared to conventional banks, impacting their ability to navigate economic shocks effectively (Bilgin et al, 2020). The study by (Rashid et al, 2017) suggests that Islamic banks have performed better than conventional banks in contributing to financial stability, indicating a potential resilience in the face of crises (Rashid et al, 2017).…”
Section: Greater Negative Impact On Islamic Banks Compared To Convent...mentioning
confidence: 99%
“…In contrast, the financial stability ratio is FDR 0.045, Bank Size is 0.001, and BI Rate is 0.001 <0.05, so it can be concluded that the null hypothesis cannot be accepted. Z-Score as a financial stability variable proved to have no average difference between before the Covid-19 pandemic and during the Covid-19 pandemic (referring to table 2), but there was a difference in the mean value of Z-Score before the Covid-19 pandemic higher than the mean value of Z-Score during the Covid-19 pandemic (referring to table 1), the position of both above the number 2675 so that it is still safe from the threshold of bankruptcy (Michael, With these results, it is understood that the level of likelihood of insolvency before the pandemic is more minor than during a pandemic and can be interpreted even though Islamic banks are resistant to crises both in principle and practice (Bilgin et al, 2020), but regulators must still pay specific attention if there is a problem because it affects stability (Lasty et al, 2019;Michael, 2017). In more sophisticated business developments, Z-Score can effectively identify indications of danger (Chiaramonte et al, 2015).…”
Section: Paired T-testmentioning
confidence: 99%
“…The findings of Nugroho & Qizam (2014) show that Islamic banks remained stable with an increasing trend during the crisis compared to conventional banks. Bilgin et al (2020) found that global economic uncertainty can increase the risk of failure. It was found that Islamic banks are immune to economic uncertainty.…”
Section: Hypothesis Developmentmentioning
confidence: 99%